The Influence of Determination of Regional Budget with Regional Head Regulations and Capital Expenditure Allocation on Capital Expenditure Realization in the Provincial APBD of the Special Capital Region of Jakarta - Pandji Sukmana (International Journal of Business and Social Science Research, 2022)
This study aimed to determine how much influence the determination of the APBD with Regional Head Regulations and the allocation partially and jointly on the realization of capital expenditures in the APBD in the Province of the Special Capital Region of Jakarta for the 2015 Fiscal Year. The research method uses a survey with a quantitative approach that is correlational. The sampling technique is Simple Random Sampling; namely, taking sample members from the population is done randomly without showing the existing strata. The number of samples in this study was 89 respondents. Based on the results of the research that has been carried out, it can be concluded that: a) Multiple Regression Analysis obtained a positive value, namely the variable of determining APBD (X1) of 0.457 and variable of allocation of capital expenditure (X2) obtained a value of 0.463. The results of the Multiple Correlation Analysis between the Variables of determining APBD (X1) and Variables of allocation of capital expenditures (X2) of 0.690. Thus, it can be said that the relationship between the independent variable and the dependent variable is strong. b) The results of hypothesis testing both partially and simultaneously, the variables of determining APBD with local government regulation (X1) and allocation of capital expenditures (X2) affect the variable of capital expenditure absorption (Y), so that Ha is confirmed, Ho is rejected. c) From the coefficient of determination test results, the result is 0.476. Thus the independent variable can explain the dependent variable by 47.6% to the dependent variable, while the rest is not examined in this study.